From Clinic to Stanza: Tracing Medical Motifs in Williams’s Poetic Practice - Saksono, Suryo Tri; Salikin, Hairus; Wardhono, Agus; Inayati, Rif’ah; Surya, Ulvia Ika; Hanifa, Siti; Harits, Imron Wakhid; Suryani, Suci (Advances in Social Sciences Research Journal, 2026)
This study explores the intersection of William Carlos Williams’s dual roles as a physician and poet, focusing on the impact of his medical career on his poetic work. By examining selected poems, the research highlights how Williams’s firsthand experiences as a doctor influence the themes, structure, and emotional depth of his poetry. Through a qualitative analytical framework, the study uncovers the presence of medical motifs, including illness, healing, and the doctor-patient relationship, and demonstrates how these elements shape both the form and content of his literary creations. The findings emphasize the unique fusion of medical observation with poetic expression in Williams’s work, illustrating how his clinical background informs his exploration of the human condition. This study contributes to the fields of literary criticism and medical humanities, offering new insights into the intersection of personal experience and artistic creation. Furthermore, it advocates for the value of interdisciplinary approaches in understanding how professional experiences can shape creative output. Future research may expand the analysis to include a broader selection of Williams’s poetry and explore comparative studies with other poet-physicians, further deepening our understanding of the interplay between medicine and literature.